The Winning of Empty Box in the 2018 Makassar Regional Head Election - Harianto, Harianto; Darmawan, Wawan Budi; Muradi, Muradi (Society, 2020)
This research discusses how the empty box won in the 2018 Makassar Regional Head Election. This phenomenon became the elections’ history where a single candidate failed to win the election. Ten political parties consisting of Functional Groups Party (Golkar), National Democratic Party (NasDem), Indonesian Democratic Party of Struggle (PDI-P), United Development Party (PPP), Crescent Star Party (PBB), Great Indonesia Movement Party (Gerindra), Prosperous Justice Party (PKS), People’s Conscience Party (Hanura), National Mandate Party (PAN), and Indonesian Justice and Unity Party (PKPI), promoted a single candidate pair. This study aims to describe how the movement of empty box volunteers in the Makassar Regional Head Election. This research uses a qualitative method. Selection of informants using a snowball sampling technique, and using social movement theory. There are three parts to this theory: 1) Complaint theory. Public disappointment over a candidate pair’s disqualification and consider the election organizer unfair; 2) Mobilizing structures theory. Analyze the voluntary movement of empty boxes to gather mass support and sympathizers during the election; and 3) Framing theory. Analyze the use of issues and methods of spreading the issue. This research found that the empty box phenomenon in Makassar Regional Head Election, unlike in the elections in other areas where the single candidate did not have an opponent, in Makassar, one of the candidate pairs was disqualified due to violation. It made the community, supporters, and the success team feels disappointed with the General Elections Commission’s decision. This disappointment also resulted in the emergence of the empty box volunteer movement. Movements of empty box volunteers to gather mass support and sympathizers through door-to-door socializing, leaflets, flyers, and banners call to action to win empty box and use social media and online media as campaign tools.